PERBANDINGAN KUALITAS HIDUP LANJUT USIA YANG TINGGAL DI PANTI JOMPO DENGAN YANG TINGGAL DI RUMAH DI KABUPATEN TAPANULI SELATAN TAHUN 2013 - Siti Fatimah Siregar; Abdul Jalil Amri Arma; Ria Masniari Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
ABSTRACT Advances in science and technology have an impact on improving the quality of life of the elderly and life expectancy, along with this, the number of elderly population has also increased. Efforts to improve the quality of life of the elderly in Indonesia could be through home care and aging institution services. The purpose of this study is determine differences in the quality of life (physical, psychological, social and environment domain) of the elderly who live in aging institution and staying at home. Study sample consisted of 38 elderly who lives in aging institution Warga Mas Titian Ridho Ilahi in Batang Angkola Tapanuli Selatan and 38 elderly who stay at home in district of Batang Angkola Pintupadang I Tapanuli Selatan. The statistical test used was the Mann Whitney test. Obtained no difference in physical quality (p=0,085) and environmental quality (0,0157) of elderly people living at aging institution and staying at home, there is a statistically significant difference in the quality of the psychology (p=0,029) and quality of social (p=0,032) of elderly people living at aging institution and staying at home, overall, there are differences in their quality between the elderly living at aging institution and staying at home (p = 0.027). Based on the results of this study are advised to continue to improve the services of psychology in the form of increased productivity, provide information to the elderly and access to health services, especially in the elderly living at aging institution. Keywords : quality of life, the elderly, aging institution